2019
DOI: 10.3390/atmos10090511
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Dust Storms with the Millimeter Wave Radar in the Taklimakan Desert

Abstract: In order to conduct real-time quantitative monitoring of dust storms, Ka-band millimeter wave radar (MMWR) was utilized for the consecutive detection of dust storms over the Taklimakan Desert from April to June 2018. The retrievals of the reflectivity factor, dust spectrum distribution and dust mass concentration were carried out with the power spectrum data detected by MMWR for three dust storm processes. The analysis shows that: The probability density distribution of dust conforms to the lognormal distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Wei et al's [30] results confer greater credibility on the results obtained from Equation (13). Therefore, for evaluation purposes, the values may be adopted conveniently, considering that the observation height for Mujlid's [26] environment conditions could not have exceeded 1.7 m, which is the average human height [31].…”
Section: Particle-concentration Equivalent Of a Dynamic Meteorological Condition (Wind Velocity)mentioning
confidence: 89%
See 2 more Smart Citations
“…Wei et al's [30] results confer greater credibility on the results obtained from Equation (13). Therefore, for evaluation purposes, the values may be adopted conveniently, considering that the observation height for Mujlid's [26] environment conditions could not have exceeded 1.7 m, which is the average human height [31].…”
Section: Particle-concentration Equivalent Of a Dynamic Meteorological Condition (Wind Velocity)mentioning
confidence: 89%
“…By substituting the reported wind speeds (and estimated errors) in the order mentioned in the earlier paragraphs into Equation ( 13 [29] was superficially mentioned without elaborating on its employability restrictions. However, assuming the same study environment as in [29], a recently published work [30] indicated that variation in SDS particle concentrations are not only limited to changing wind speeds but can be observed in their vertical distribution as well. Wei et al's [30] real-time measurements revealed that during the SDS period for heights less than 100 m, the concentrations ranged between 1220 µg/m 3 and 42,146 µg/m 3 .…”
Section: Particle-concentration Equivalent Of a Dynamic Meteorological Condition (Wind Velocity)mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2013) have used wind pro ling radar to study the dust storm over Taklimakan desert in detail. Ming et al (2019) have used a groundbased multimeter wave radar to detect dust storm in the same desert region, where re ectivity factors of dust storms were better estimated in real time in comparison with satellite remote sensing. However, the spatial movement of the dust storm cannot be comprehended by ground based instruments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, as we all know, microwave radar is widely distributed in monitoring stations all over the world, and it is an important means of meteorological monitoring, and plays a very important role in sudden and disastrous monitoring, forecasting and alarm. Recent field measurements have found that effective echoes have been received when using microwave radar to measure sandstorms, which provides an idea for using microwave radar to detect sandy dust weather (Wang et al, 2017;Ming et al, 2019). In addition, some studies have found that dust particles carry a large amount of net charge (Zheng et al, 2003;Bo et al, 2014;Zhang and Zhou, 2020), and the charge carried by particles will enhance the backscattering of radar waves and the attenuation of radar waves on the back-and-forth path.…”
mentioning
confidence: 99%